Past, present and future of chamois science. Issue 4 (22nd April 2022) - Corlatti, L.; Iacolina, L.; Safner, T.; Apollonio, M.; Buzan, E.; Ferretti, F.; Hammer, S. E.; Herrero, J.; Rossi, L.; Serrano, E.; Arnal, M. C.; Brivio, F.; et al.
Abstract : The chamois Rupicapra spp. is the most abundant mountain ungulate of Europe and the Near East, where it occurs as two species, the northern chamois R. rupicapra and the southern chamois R. pyrenaica . Here, we provide a state‐of‐the‐art overview of research trends and the most challenging issues in chamois research and conservation, focusing on taxonomy and systematics, genetics, life history, ecology and behavior, physiology and disease, management and conservation. Research on Rupicapra has a longstanding history and has contributed substantially to the biological and ecological knowledge of mountain ungulates. Although the number of publications on this genus has markedly increased over the past two decades, major differences persist with respect to knowledge of species and subspecies, with research mostly focusing on the Alpine chamois R. r. rupicapra and, to a lesser extent, the Pyrenean chamois R. p. pyrenaica . In addition, a scarcity of replicate studies of populations of different subspecies and/or geographic areas limits the advancement of chamois science. Since environmental heterogeneity impacts behavioral, physiological and life history traits, understanding the underlying processes would be of great value from both an evolutionary and conservation/management standpoint, especially in the light of ongoing climatic change. Substantial contributions to this challenge may derive from a quantitative assessment of reproductive success, investigation of fine‐scale foraging patterns, and a mechanistic understanding of disease outbreak and resilience. For improving conservation status, resolving taxonomic disputes, identifying subspecies hybridization, assessing the impact of hunting and establishing reliable methods of abundance estimation are of primary concern. Despite being one of the most well‐known mountain ungulates, substantial field efforts to collect paleontological, behavioral, ecological, morphological, physiological and genetic data on different populations and subspecies are still needed to ensure a successful future for chamois research and conservation.